2000
DOI: 10.1590/s1415-47572000000100032
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome numbers in Bromeliaceae

Abstract: The present study reports chromosome numbers of 17 species of Bromeliaceae, belonging to the genera Encholirium, Bromelia, Orthophytum, Hohenbergia, Billbergia, Neoglaziovia, Aechmea, Cryptanthus and Ananas. Most species present 2n = 50, however, Bromelia laciniosa, Orthophytum burle-marxii and O. maracasense are polyploids with 2n = 150, 2n = 100 and 2n = 150, respectively, while for Cryptanthus bahianus, 2n = 34 + 1-4B. B chromosomes were observed in Bromelia plumieri and Hohenbergia aff. utriculosa. The chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 4 publications
4
24
1
3
Order By: Relevance
“…All the species presented a diploid number 2nϭ50, except for Orthophytum albopictum and Neoglaziovia variegata, which are tetraploids, 2nϭ100 ( (Lindschau 1933, Sharma and Ghosh 1971, Brown et al 1984, Varadarajan and Brown 1985, Brown and Gilmartin 1986, 1989, Marchant 1967, Brown et al 1997, Baracho and Guerra 2000, Gitaí et al 2000, Cotias de Oliveira et al 2000. These counts showed nϭ25, 2nϭ50 in about 68 species analyzed and only five polyploids with 2nϭ100, 150.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…All the species presented a diploid number 2nϭ50, except for Orthophytum albopictum and Neoglaziovia variegata, which are tetraploids, 2nϭ100 ( (Lindschau 1933, Sharma and Ghosh 1971, Brown et al 1984, Varadarajan and Brown 1985, Brown and Gilmartin 1986, 1989, Marchant 1967, Brown et al 1997, Baracho and Guerra 2000, Gitaí et al 2000, Cotias de Oliveira et al 2000. These counts showed nϭ25, 2nϭ50 in about 68 species analyzed and only five polyploids with 2nϭ100, 150.…”
Section: Resultsmentioning
confidence: 94%
“…al. 1984, Brown and Gilmartin 1989, Brown et al 1997, Baracho and Guerra 2000, Gitaí et al 2000, Cotias de Oliveira et al 2000, Palma-Silva 2003. The majority of the 101 species counts have been nϭ25.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Bromeliaceae, cytogenetic studies are rare and chromosome numbers have been reported for no more than 12% of the species (Lindschau 1933;Gauthé 1965;Weiss 1965;Marchant 1967;Sharma & Ghosh 1971;McWilliams 1974;Brown et al 1984;Varadarajan & Brown 1985;Brown & Gilmartin 1986, 1989Lin et al 1987;Brown et al 1997;Cotias-de-Oliveira et al 2000Ramírez-Morillo & Brown 2001;Palma-Silva et al 2004;Bellintani et al 2005;Gitaí et al 2005). The chromosomes are small with sizes varying between 0.23 mm and 1.5 mm (Cotias-de-Oliveira et al 2000;Ceita et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, all studies based on meiotic (Brown & Gilmartin 1983, 1986, 1989Brown et al 1997;Palma-Silva et al 2004 Chromosome numbers have been reported for only six species of Orthophytum, revealing an euploid series (i.e. polyploids in exact multiples of the basic number) of 2n = 2x = 50, 2n = 4x = 100 and 2n = 6x = 150 chromosomes (Ramírez-Morillo & Brown 2001;Cotias-de-Oliveira et al 2000Bellintani et al 2005;Gitaí et al 2005). Polyploidy, or genomic duplication, is a common and continuous phenomenon in plant evolution, and about 70% of the angiosperms are polyploids (Leitch & Bennett 1997).…”
Section: Introductionmentioning
confidence: 99%